PENGARUH PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SCARLETT WHITENING PADA KONSUMEN KOTA BLITAR - Nurul Farida (Universitas Islam Balitar, 2022)
This study aims to determine the effect of product, price, and promotion on purchasing decisions of Scarlett Whitening in Blitar Regency. Based on the results of the t test, the product shows a Sig value of 0.287 and the t count shows a value of 1.075, it means that the Sig value is greater than the probability value of 0.05 (0.287 > 0.05) and the t count is smaller than the t table (1.075 < 2.00324). The price variable of the t test value shows a Sig value of 0.000 and t count shows a value of 5.376, it means that the Sig value is smaller than the probability value of 0.05 (0.000 < 0.05) and t count is greater than t table (5.376 < 2.00324) and the variable Promotional t test shows a Sig value of 0.000 and t arithmetic shows a value of 4.547, it means that the Sig value is less than the probability value of 0.05 (0.000 < 0.05) and t count is greater than t table 4.547 < 2.00324). The results of the F test show that the calculated f value of 80.362 is greater than the f table of 2.38 and with a significance of 0.000. Because f count > f table and significance level < 0.05, the regression model can be said that Product, Price and Promotion simultaneously or simultaneously affect on purchasing decisions, while the results of the coefficient of determination test (R2) obtained a value of 0.817 or 81 .7% while 18.3% is influenced by other variables.